'Archaeologies of Archaeologies of the Contemporary Past': An Interview with Victor Buchli and Gavin Lucas - González-Ruibal, Alfredo; Harrison, Rodney; Holtorf, Cornelius; Wilkie, Laurie (Journal of Contemporary Archaeology, 2015)
This interview with Victor Buchli and Gavin Lucas was undertaken over email during the Summer / Autumn of 2013 and coordinated by Alfredo González-Ruibal on behalf of the editorial team: Alfredo González-Ruibal, Rodney Harrison, Cornelius Holtorf and Laurie Wilkie. An initial set of questions was drafted and agreed amongst members of the editorial team, and a series of follow-up questions (indicated by the presence of author’s initials) were subsequently posed in cases where individuals hoped the interviewees might expand on particular points. These have been maintained in the text to allow the reader to follow the various threads which each interviewer chose to pursue.